Emerging translational strategies and challenges for enhancing regulatory T cell therapy for graft-versus-host disease - Hippen, Keli L.; Hefazi, Mehrdad; Larson, Jemma H.; Blazar, Bruce R. (Frontiers in Immunology, 2022)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a curative therapy for many types of cancer. Genetic disparities between donor and host can result in immune-mediated attack of host tissues, known as graft versus host disease (GVHD), a major cause of morbidity and mortality following HSCT. Regulatory CD4+ T cells (Tregs) are a rare cell type crucial for immune system homeostasis, limiting the activation and differentiation of effector T cells (Teff) that are self-reactive or stimulated by foreign antigen exposure. Adoptive cell therapy (ACT) with Treg has demonstrated, first in murine models and now in patients, that prophylactic Treg infusion can also suppress GVHD. While clinical trials have demonstrated Treg reduce severe GVHD occurrence, several impediments remain, including Treg variability and practical need for individualized Treg production for each patient. Additionally, there are challenges in the use of in vitro expansion techniques and in achieving in vivo Treg persistence in context of both immune suppressive drugs and in lymphoreplete patients being treated for GVHD. This review will focus on 3 main translational approaches taken to improve the efficacy of tTreg ACT in GVHD prophylaxis and development of treatment options, following HSCT: genetic modification, manipulating TCR and cytokine signaling, and Treg production protocols. In vitro expansion for Treg ACT presents a multitude of approaches for gene modification to improve efficacy, including: antigen specificity, tissue targeting, deletion of negative regulators/exhaustion markers, resistance to immunosuppressive drugs common in GVHD treatment. Such expansion is particularly important in patients without significant lymphopenia that can drive Treg expansion, enabling a favorable Treg:Teff ratio in vivo. Several potential therapeutics have also been identified that enhance tTreg stability or persistence/expansion following ACT that target specific pathways, including: DNA/histone methylation status, TCR/co-stimulation signaling, a d IL-2/STAT5 signaling. Finally, this review will discuss improvements in Treg production related to tissue source, Treg subsets, therapeutic approaches to increase Treg suppression and stability during tTreg expansion, and potential for storing large numbers of Treg from a single production run to be used as an off-the-shelf infusion product capable of treating multiple recipients.